Mirizzi’s Syndrome - Fachrull -; Anggilia Stephanie; E Mudjaddid (The Indonesian Society for Digestive Endoscopy, 2015)
Mirizzi’s syndrome was an obstruction caused by gallstone located in gallbladder neck (or cystic duct) or outside gallbladder that caused a dilatation of gallbladder and narrowing of adjacent duct, sometimes with the presence of cholecystocholedochal fistula. Mirizzi’s syndrome was a rare complication of gallbladder stone. We reported a 42 years old woman complained progressive icteric sclera. Patients also complained dark urine and light stool. During physical examination, we found an icteric sclera, pain in right upper quadrant (visual analogue scale/VAS 3), and generalized icterus (greenish yellow). Complete examination revealed a Mirizzi’s syndrome.